Fine-Tuning of Neuronal Ion Channels-Mapping of Residues Involved in Glucose Sensitivity of Recombinant Human Glycine Receptors - Hussein, Rama Ashraf; Ahmed, Marwa; Sticht, Heinrich; Breitinger, Hans Georg; Breitinger, Ulrike (Acs Chemical Neuroscience, 2020)
The inhibitory glycine receptor (GlyR) mediates synaptic inhibition in the spinal cord, brain stem, and other regions of the mammalian central nervous system. Glucose was shown to potentiate α1 GlyRs by interacting with K143. Here, additional amino acids involved in glucose modulation were identified using a structure-based approach of site-directed mutagenesis followed by whole-cell patch-clamp analysis. We identified two additional lysine residues in the α1 GlyR extracellular domain, K16 and K281, that were involved in glucose modulation. Mutation of either residue to alanine abolished glucose potentiation. Residue K281 is located in the same pocket as K143 and could thus contribute to glucose binding. The double mutant K143A-K281A showed a 6-fold increase of EC50, while EC50 of both single mutants K143A and K281A was only slightly increased (1.7- and 1.3-fold, respectively). K16 is located at an analgesic binding site that is distant from the agonist or glucose sites, and the K16A mutation may generate a receptor species that is not potentiated. GlyR position α1-S267 is close to the postulated glucose binding site and known for interactions with ethanol and anesthetics. In the presence of glucose, GlyR α1 mutants S267A, S267I, and S267R showed potentiation, no effect, and reduction of current responses, respectively. This pattern follows that of ethanol modulation and suggests that the interaction sites of glucose and ethanol are identical or located close to each other. Our results support the presence of a distinct binding site for glucose on the glycine receptor, overlapping with the ivermectin/ethanol binding pocket near the transmembrane region and the TM2-3 loop.
CRIS-Team Scopus Importer:2020-11-06
Keywords: ethanol modulation; glucose modulation; Glycine receptor; ion channel function; ion channel potentiation; lysine residues; modulatory sites; mutagenesis; structure modeling